2017
DOI: 10.11113/sh.v9n1-5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Pembangunan Modul Kemahiran Berfikir Aras Tinggi di dalam Mata Pelajaran Sains Sekolah Rendah: Analisis Keperluan Guru

Abstract: Teaching Higher Order Thinking Skills (HOTS) has its own challenges and need to be emphasized in the curriculum as it is one of the skills of the 21st century. HOTS is among six main characteristics of students who aspire Ministry of Education to succeed globally. However, studies on the effectiveness of the module KBAT in science subjects still not carried out. Hence, the purpose of this study was to develop and evaluate the effectiveness of teaching modules based on higher order thinking skills in science su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The findings of the data analysis found that instructors face difficulties in adapting lesson planning to the different abilities of students. This situation makes it difficult for lecturers to identify teaching methods that are appropriate for student differences and requires researchers to identify methods appropriate to the situation and appropriate to the studies done by Hassan et al (2017) and Sieglov (2019), who agreed that the needs analysis helps detect problems occurring in a study. Apart from that, obtaining answers to the issues that cause the RPH building drawing guidelines needs to be developed in this study.…”
Section: Initial Investigationmentioning
confidence: 99%
“…The findings of the data analysis found that instructors face difficulties in adapting lesson planning to the different abilities of students. This situation makes it difficult for lecturers to identify teaching methods that are appropriate for student differences and requires researchers to identify methods appropriate to the situation and appropriate to the studies done by Hassan et al (2017) and Sieglov (2019), who agreed that the needs analysis helps detect problems occurring in a study. Apart from that, obtaining answers to the issues that cause the RPH building drawing guidelines needs to be developed in this study.…”
Section: Initial Investigationmentioning
confidence: 99%
“…Higher-order thinking skills (HOTS) in mathematics has received serious attention by the Ministry of Education (MoE) Malaysia, as evident by its explicit inclusion into the national education curriculum (Hassan et al, 2017). Students' ability to think using higher-order thinking skills in mathematics serves as an important employability factor to face the growing challenges in the employment industry (Gani, 2018).…”
Section: Higher-order Thinking Skills In Mathematicsmentioning
confidence: 99%